Analysis of applying ultrasonic frequency on a desktop FDM nozzle - Maidin, Shajahan; Abdul Aziz, Khairul Fahmi; Muhamad, Muhammad Kazimi; E. Pei (Trans Tech Publications, 2015)
Fused deposition modeling (FDM) is an additive manufacturing (AM) process that has an economical advantage compared to other AM processes. However, its biggest drawback is that it requires post processing to achieve a good surface finish. Ultrasound has been applied in various conventional machining processes and produces a good surface finish. However, the application of ultrasound to AM has not been sufficiently explored. This research aims to investigate the application of using ultrasound technology for a desktop FDM system. The idea is to transmit high vibration from the ultrasonic transducer to the FDM system's nozzle, and the objective is to examine whether the nozzle is able to withstand the high vibration being transmitted. Computeraided design (CAD) software used to develop the 3D model of the extrusion nozzle component and a computer-aided engineering (CAE) software was used to perform static and vibration analysis. A frequency range of 20 to 30kHz and 30 to 40kHz was applied to the nozzle and it was found that the nozzle was able to withstand frequencies up to 40 kHz of vibration. In addition, the lowest Factor of Safety (FoS) obtained was 18.8975, concluding that the nozzle of FDM can withstand the high vibration transmitted from the ultrasonic transducer.